Pengaruh Sustainability Report, Good Corporate Governance, Dan Profitability Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sektor Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia BEI Periode 2020 – 2022 - Sintha Ayu Pithaloka; Maria Yovita R. Pandin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to examine the effect of sustainability report, good corporate governance, and profitability on the value of manufacturing companies in the food and beverage sector in 2020-2022. The population in this study is 33 food and beverage sector manufacturing companies in 2020-2022. This type of research is quantitative research. The research sampling technique uses the purposive sampling method, namely sample selection based on predetermined criteria so that 12 companies are obtained as research samples. This study used secondary data obtained from the annual report of the official website of the Indonesia Stock Exchange (IDX) and the website of the company that was the research sample. This analysis technique uses SPSS software version 26. The results showed that sustainability report and good corporate governance did not affect company value, profitability had a positive and significant effect on company value.